Shadow bank, risk-taking, and real estate financing: Evidence from the online loan market - DENG, Xiaoying (Institutional Knowledge at Singapore Management University, 2024)
This paper examines whether and how individual risk-taking behavior affects real estate financing through shadow banks. Using the loan data from an online platform in China, we show that riskier households tend to employ online loans to meet the increasing down-payment in their home purchase. Individual investors are likely to fund riskier real estate loans with higher expected returns. Real estate loans experience higher ex-post default rates than other types of loans. The effect is more pronounced during the period of credit constraints.